A SYSTEMATİC ANALYSİS OF THE SOCİAL NETWORK EVOLUTİON LİTERATURE (Third Sector Social Economic Review, 2021)
The aim of this study is to monitor the current status and development of the literature on social networking evolution. The study focuses on topics of ""network change"" and ""network development"", especially in the management and business categories. To this end, a total of 167 studies between 1996 - 2021 were analyzed in depth using bibliometric analysis. In this context, analyzes were made under the titles such as the productivity and evolution of the field, the most relevant authors, the most global cited articles, the co-occurance network, and the most relevant sources. As a result of the analysis, it is observed that there are few studies in the fields of management and business and more importance is given to performance, dynamics and social networks. In addition, a significant part of the study focuses on interorganizational relations.
Keywords: network evolution; network change; bibliometric; social network theory; management; business; Web of Science (WoS)